Low‐energy collision‐induced dissociation (low‐energy CID), collision‐induced dissociation (CID), and higher energy collision dissociation (HCD) mass spectrometry for structural elucidation of saccharides and clarification of their dissolution mechanism in DMAc/LiCl. (9th July 2018) - Bayat, Parisa; Lesage, Denis; Cole, Richard B.
Abstract: The dissolution mechanism of oligosaccharides in N, N ‐dimethylacetamide/lithium chloride (DMAc/LiCl), a solvent used for cellulose dissolution, and the capabilities of low‐energy collision‐induced dissociation (low‐energy CID), collision‐induced dissociation (CID), and higher energy collision dissociation (HCD) for structural analysis of carbohydrates were investigated. Comparing the spectra obtained using 3 techniques shows that, generally, when working with monolithiated sugars, CID spectra provide more structurally informative fragments, and glycosidic bond cleavage is the main pathway. However, when working with dilithiated sugars, HCD spectra can be more informative providing predominately cross‐ring cleavage fragments. This is because HCD is a nonresonant activation technique, and it allows a higher amount of energy to be deposited in a short time, giving access to more endothermic decomposition pathways as well as consecutive fragmentations. The difference in preferred dissociation pathways of monolithiated and dilithiated sugars indicates that the presence of the second lithium strongly influences the relative rate constants for cross‐ring cleavages vs glycosidic bond cleavages, and disfavors the latter. Regarding the dissolution mechanism of sugars in DMAc/LiCl, CID and HCD experiments on dilithiated and trilithiated sugars reveal that intensities of product ions containing 2 Li + or 3 Li +, respectively, are higher than those bearing only 1 Li + . In addition, comparing the fragmentation spectra (both HCD and CID) of LiCl‐adducted lithiated sugar and NaCl‐adducted sodiated sugar shows that while, in the latter case, loss of NaCl is dominant, in the former case, loss of HCl occurs preferentially. The compiled evidence implies that there is a strong and direct interaction between lithium and the saccharide during the dissolution process in the DMAc/LiCl solvent system.